Clinical indicators of acute deterioration in persons who reside in residential aged care facilities: A rapid review. Issue 1 (20th October 2022) - Chambers, Shirley; Spooner, Amy; Parker, Christina; Jack, Leanne; Schnitker, Linda; Beattie, Elizabeth; Yates, Patsy; MacAndrew, Margaret
Abstract: Purpose: To identify the clinical indicators of acute deterioration in residents and the factors that influence residential aged care facility staff's identification of these. Design: Rapid review and narrative synthesis. Methods: The WHO and Cochrane Rapid Review Methods Group recommendations guided the review processes. CINAHL, Medline, PubMed, and the Cochrane Library were searched from 2000 to January 2022. Data related to clinical indicators of deterioration were categorized using the Airway, Breathing, Circulation, Disability, Exposure assessment framework, and factors influencing detection were grouped as consumer (resident and family), aged care workforce, and organization factors. Results: Twenty publications were included of which 14 informed clinical indicators; nine highlighted factors that influence staff's identification of these and three informed both. Included article were collectively below moderate quality. Most clinical indicators were grouped into the 'Disability' category with altered level of consciousness, behavior, and pain identified most frequently. Few studies reported more traditional indicators of deterioration used in the general population – changes in vital signs. The most common factors influencing the detection of acute deterioration were organizational and workforce‐related including resource, knowledge, and confidence deficits. Conclusion: Findings suggest subtle changes in resident's health status, rather than focusing primarily on physiologic parameters used in early warning tools for acute care settings, should be recognized and considered in the design of early warning tools for residential aged care facilities. Clinical Relevance: Early warning tools sensitive to the unique needs of residents and support for aged care facility staff are recommended to improve the capacity of aged care facility care staff to identify and manage acute deterioration early to avoid hospitalization.